Economic survey of Japan (1993-1994) - a challenge to new frontiers beyond the severe adjustment process : (summary) (Economic Planning Agency [s.n.], 1994)
Views from a short-term perspective, the Japanese economy fiscal 1993. Looks at the characteristics and background of the current downturn from a medium-term viewpoint. Takes up the long-term and structural issues that the Japanese economy faces.
DC